Metodika práce s třídním kolektivem v inkluzivní třídě se zaměřením na žáky se zrakovým postižením Metodická příručka - Röderová, Petra (Masaryk University Press, 2020)
Title in English: Methodology of Classroom Management in Inclusive Classroom with a Focus on Pupils with Visual Disability: Methodological Manual The text offers information on visual impairment and its impact on the educational process and school work. The text provides background information for ordinary school teachers not only about the special educational needs of a pupil with visual impairment, but also about how to support the inclusive climate of the classroom in accepting diversity, cooperating pupils and communicating with each other in the classroom. The text also offers information on the role of drama in inklusive education